2008
DOI: 10.1002/hipo.20524
|View full text |Cite
|
Sign up to set email alerts
|

Rat hippocampal theta rhythm during sensory mismatch

Abstract: It has been suggested that sensory mismatch induces motion sickness, but its neural mechanisms remain unclear. To investigate this issue, theta waves in the hippocampal formation (HF) were studied during sensory mismatch by backward translocation in awake rats. A monopolar electrode was implanted into the dentate gyrus in the HF, from which local field potentials were recorded. The rats were placed on a treadmill affixed to a motion stage translocated along a figure 8-shaped track. The rats were trained to run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…The present study provides additional evidence with respect to a role of the HD system in directional processing; the rodent HD system extracts different types of directional information (Figure 9) in different reference frames in a conflicting situation. The previous studies suggest the rats could adapt to backward translocation (Zou et al, 2009a; Aitake et al, 2011), and hippocampal neurons showed plastic changes in place fields after repeated experience of backward translocation in the same setup as in the present study (Zou et al, 2009b). The HD neurons reported in the present study might play important roles for spatial updating during the backward translocation.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The present study provides additional evidence with respect to a role of the HD system in directional processing; the rodent HD system extracts different types of directional information (Figure 9) in different reference frames in a conflicting situation. The previous studies suggest the rats could adapt to backward translocation (Zou et al, 2009a; Aitake et al, 2011), and hippocampal neurons showed plastic changes in place fields after repeated experience of backward translocation in the same setup as in the present study (Zou et al, 2009b). The HD neurons reported in the present study might play important roles for spatial updating during the backward translocation.…”
Section: Discussionsupporting
confidence: 71%
“…However, it might be unlikely; first, the previous studies reported that although the backward movement increased hippocampal theta and sympathetic nervous activity, which corresponds to symptoms in motion sickness, the activity returned to the baseline level after repeated experience of this situation (Zou et al, 2009a; Aitake et al, 2011). This suggests that the rats could adapt to this situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies in alert animals have reported that theta rhythm in the frequency range of 6–9 Hz can be recorded during movement (see Zou et al, 2009 for a review). In fact, theta frequency has been shown to increase with increasing speed of locomotion (Jeewajee et al, 2008; Lever et al, 2009).…”
Section: Effects Of Vestibular Lesions On Head Direction Cell and Plamentioning
confidence: 99%